Ecological utilization of the weed - tithonia diversifolia and sustainability of the paper industry in Nigeria (2000)
Tithonia diversifolia is found growing abundantly within the forest zone of Nigeria. The evaluation of the pulp and paper making properties of T. diverisifolia showed average fibre length, width, wall thickness and lumen of 827.66 ± 186.40αµm, 20.29 ± 3.92 αµm, 3.96 ± 0.28 αµm and 12.16 ± 3.96 µm respectively. This short fibre length and small wall thickness of T. diversifolia made it unsuitable for making strong papers. However, it is good material for making newsprints, toilet tissues, serviette papers, packing cartons and egg crates. This will go a long way towards improving the welfare and living conditions of Nigerian given that paper is a civilised material.